2020
DOI: 10.1002/jmv.26301
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytokines with hepatitis B virus and its antigen

Abstract: To investigate the characteristics of cytokines in patients with different HBV infection status and their correlation with HBV DNA, HBsAg, and HBeAg levels. Peripheral blood samples were collected from patients with chronic HBV infection in immune tolerance phase (IT), HBeAg‐positive chronic hepatitis B (CHB), and acute hepatitis B (AHB) groups, and levels of cytokines were detected by Luminex technique, and analyzed by FLEXMAP 3D analyzer. The correlation between cytokines and HBV DNA load, HBsAg, HBeAg, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…The baseline HBsAg and HBeAg levels in the ALT normalization group were significantly lower than that in the non-normalization group. The baseline IL-10 and TGF-b1 in the ALT normalization group were lower than that in the ALT non-normalization group, while the baseline ALT level and IFN- (14,15,28), and the efficacy of NA treatment is related to the immune and viral factors of patients (2,6,7). At 3 and 6 months after treatment, the IFN-g level of the ALT normalization group was significantly higher than that in the non-normalization group.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The baseline HBsAg and HBeAg levels in the ALT normalization group were significantly lower than that in the non-normalization group. The baseline IL-10 and TGF-b1 in the ALT normalization group were lower than that in the ALT non-normalization group, while the baseline ALT level and IFN- (14,15,28), and the efficacy of NA treatment is related to the immune and viral factors of patients (2,6,7). At 3 and 6 months after treatment, the IFN-g level of the ALT normalization group was significantly higher than that in the non-normalization group.…”
Section: Discussionmentioning
confidence: 88%
“…At 3 and 6 months after treatment, the IFN-g level of the ALT normalization group was significantly higher than that in the non-normalization group. Given that IFN-g is an important cytokine for cellular immunity (14,25,28,29), the increase in IFN-g suggests that ETV can restore part of cellular immune function by reducing HBV DNA load (29). Logistic regression analyzed risk factors related to whether the ALT is normal after 48 weeks of ETV treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mononuclear macrophages are important immune cells involved in liver in ammation, and the increased activity of these mononuclear macrophages leads to an increase in IL-10 level. [9,22] All cytokines were included in the analysis of risk factors for CHB patients with chronic HBV infection in immune tolerant phase and chronic hepatitis B. In multivariate logistic regression analysis, TGF-β 1 and TGF-β 2 were statistically signi cant (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 has been demonstrated to serve important roles in HBV induces liver fibrosis via the TGF-β1/miR-21-5p pathway WENTING LI 1,2* , XIAOLAN YU 2,3* , XILIU CHEN 4* , ZHENG WANG 5 , MING YIN 2,6 , ZONGHAO ZHAO 1,2 and CHUANWU ZHU 7 hepatic stellate cell (HSC) activation, which is a key event in liver fibrosis (11,12). Accumulating evidence suggested that HBV infection may promote TGF-β1 production by hepatocytes, which in turn activates HSCs and accelerates liver fibrosis (13)(14)(15). HSCs is the predominant cell type responsible for liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%